Characterizing fentanyl-related overdoses and implications for overdose response: Findings from a rapid ethnographic study in Vancouver, Canada. (1st December 2018) - Mayer, Samara; Boyd, Jade; Collins, Alexandra; Kennedy, Mary Clare; Fairbairn, Nadia; McNeil, Ryan
Highlights: Illicit fentanyl use characterized as distinct from prior opioid use experiences. Rapid onset and potency characterized experiences of fentanyl use and overdose. Fentanyl-related overdoses pose unique challenges for frontline overdose response. Challenges included overdose identification, body and chest rigidity, naloxone dose. Abstract: Background: North America is experiencing an opioid overdose epidemic, fuelled by the proliferation of fentanyl, related analogues, and fentanyl-adulterated opioids. British Columbia, Canada has similarly experienced a rapid increase in the proportion of opioid overdose deaths associated with fentanyl. This study builds off of research characterizing fentanyl exposure to further explore the presentation of fentanyl use and related overdoses among people who use drugs. Methods: From December 2016 to April 2017, rapid ethnographic fieldwork was conducted in Vancouver, Canada to examine the implementation of low-threshold overdose prevention sites, where people use drugs under the supervision of staff and peers trained to respond to overdose. Data collection included 185 h of ethnographic observation and in-depth interviews with 72 people who inject drugs, 44 of whom reported experiencing an overdose in the year prior to the interviews. Results: While most participants had experienced previous opioid-related overdose, they characterized how fentanyl was markedly distinct in terms of: potency, and rapid onset. Ethnographic observations and participant narratives highlighted how fentanyl use and related overdoses had implications for frontline response, including: rapid onset, multiple concurrent overdoses, body and chest rigidity, and the need to administer larger doses of naloxone. Conclusions: Participant narratives and observational data documented distinct symptoms for fentanyl-attributed overdoses compared to other opioid related overdose events, which had implications for response. Findings may serve to inform best practices in responding to fentanyl-related overdoses including; the provision of oxygen and effective doses of naloxone, and also considerations regarding overdose identification.